2022
DOI: 10.1021/acssuschemeng.2c04409
|View full text |Cite
|
Sign up to set email alerts
|

Beckmann Rearrangement with Improved Atom Economy, Catalyzed by Inexpensive, Reusable, Bro̷nsted Acidic Ionic Liquid

Abstract: Inexpensive protic ionic liquids, synthesized from di- or triamines and excess sulfuric acid, were used as solvents and catalysts for the Beckmann rearrangement. The use of ionic liquids in place of oleum or sulfuric acid allowed the base neutralization step, which is required in the conventional Beckmann rearrangement, to be entirely avoided, thereby dramatically improving the atom economy. Using a biphasic water/organic solvent extraction system, it was possible to recover and reuse the ionic liquid. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The composition of the Brønsted acidic PIL, [Hpy][HSO 4 ]·H 2 SO 4 , was one of the two standard acidic compositions used in our earlier catalytic studies. 5,8–10 The aim of this work was to elucidate its structure (3D network vs . discrete anionic clusters) and understand how differences in the liquid structure of this PIL and sulfuric acid account for their different miscibilities with the ester product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of the Brønsted acidic PIL, [Hpy][HSO 4 ]·H 2 SO 4 , was one of the two standard acidic compositions used in our earlier catalytic studies. 5,8–10 The aim of this work was to elucidate its structure (3D network vs . discrete anionic clusters) and understand how differences in the liquid structure of this PIL and sulfuric acid account for their different miscibilities with the ester product.…”
Section: Resultsmentioning
confidence: 99%
“…A technoeconomic assessment concluded that triethylammonium hydrogensulfate, [HN 222 ][HSO 4 ], could be produced for as little as US$0.78 kg −1 , comparable to many organic solvents in commercial use. 1–4 Ionic liquids formulated from di- and tri-alkylamines with excess sulfuric acid were postulated to be even cheaper, 5 dispensing with the still-popular misconception that ionic liquids are, generically, too expensive for mainstream industrial use. 6…”
Section: Introductionmentioning
confidence: 99%
“…Du et al [93] described the Beckmann rearrangement for the synthesis of caprolactam in the presence of ionic liquid made up of sulfonyl chloride functionalized ionic materials. BMImPF 6 , can also be utilized as medium to facilitate the contact between substrate and catalyst but the yield produced was not good.…”
Section: Ionic Liquidmentioning
confidence: 99%
“…Further, it is predicted that DESs can be successfully adapted for various applications, including dissolution and processing biopolymers, inorganic synthesis, or 3D printing . Alongside the aforementioned reasons, low costs and low maintenance make DESs excellent candidates for utilization on the industrial scale, which is the main barrier in the case of most ILs. …”
Section: Deep Eutectic Solvents: From Chemistry To Bioinspired Synthesismentioning
confidence: 99%